Effective Ways of Working with Children and their Families - Hill, Malcolm (London : Jessica Kingsley, 1999)
This text examines the latest evidence about the most sucessful forms of intervention when working with children and their families. The book covers a wide range of methods and services with emphasis on helping children with known problems.
Includes bibliographical references and index.
Keywords: Children -- Services for -- Great Britain; Family -- Services for -- Great Britain; Social work with children -- Great Britain; Family social work -- Great Britain; Society